2022
DOI: 10.3389/fsoil.2022.909530
|View full text |Cite
|
Sign up to set email alerts
|

Root Border Cells as a Convenient Single Cell System to Study Plant-Environmental Interactions: A Case Study for Aluminum Tolerance

Abstract: Root border cells (RBCs) are a group of cells that originated from the root cap meristem, which are developed by genetic regulation and play a variety of biological functions. Being composed of a homologous single cell population with high metabolic activity and intact cell walls, RBCs represent a highly useful tool for studying various aspects of plant mineral absorption and utilization, as well as plant-soil-microbiome interactions in the rhizosphere. Research on RBCs also promise to become a hotspot in the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
2

Relationship

2
0

Authors

Journals

citations
Cited by 2 publications
(6 citation statements)
references
References 67 publications
0
6
0
Order By: Relevance
“…It has been speculated that there is a strong relationship between the generation, quantity and survival rate of RBCs and the meristem structure types. Feng et al [7] analyzed the number and activity of RBCs of 30 varieties of 11 different species including Solanaceae, Leguminosae, Cucurbitaceae, Geamineae, Laguminosae, and Pinaceae. By combining Hawes and Groot's study [6,7], Hamamoto et al [15] found that the number and activity of RBCs in open (including basic open-and semi-open) type species were higher than that in closed type species.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…It has been speculated that there is a strong relationship between the generation, quantity and survival rate of RBCs and the meristem structure types. Feng et al [7] analyzed the number and activity of RBCs of 30 varieties of 11 different species including Solanaceae, Leguminosae, Cucurbitaceae, Geamineae, Laguminosae, and Pinaceae. By combining Hawes and Groot's study [6,7], Hamamoto et al [15] found that the number and activity of RBCs in open (including basic open-and semi-open) type species were higher than that in closed type species.…”
Section: Discussionmentioning
confidence: 99%
“…Feng et al [7] analyzed the number and activity of RBCs of 30 varieties of 11 different species including Solanaceae, Leguminosae, Cucurbitaceae, Geamineae, Laguminosae, and Pinaceae. By combining Hawes and Groot's study [6,7], Hamamoto et al [15] found that the number and activity of RBCs in open (including basic open-and semi-open) type species were higher than that in closed type species. Thus, the number and viability of RBCs may be highly related to the structure of meristematic tissue.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Their production is regulated by genetics and plays a range of biological functions. 3 , 36 , 37 Herein, the method of assembling nano-SiO 2 particles onto the cell wall through LBL and PEI technology by using RBCs as model cells is illustrated in Figure 1 .
Figure 1.
…”
Section: The Concept Function and Bionics Of Biomineralizationmentioning
confidence: 99%
“…Many crops have toxic reactions to the micromolar concentrations of aluminum. 36 At present, more than 40% of cultivated land in the world is endangered by aluminum. 4 The main site of the toxic effect of aluminum on root growth is the root tip.…”
Section: Biomineralization and Mechanism Of Plant Aluminum Tolerancementioning
confidence: 99%